A potential wound‐healing‐promoting peptide from salamander skin. Issue 9 (27th May 2014) - Mu, Lixian; Tang, Jing; Liu, Han; Shen, Chuanbin; Rong, Mingqiang; Zhang, Zhiye; Lai, Ren
Abstract : Although it is well known that wound healing proceeds incredibly quickly in urodele amphibians, such as newts and salamanders, little is known about skin‐wound healing, and no bioactive/effector substance that contributes to wound healing has been identified from these animals. As a step toward understanding salamander wound healing and skin regeneration, a potential wound‐healing‐promoting peptide (tylotoin; KCVRQNNKRVCK) was identified from salamander skin of Tylototriton verrucosus. It shows comparable wound‐healing‐promoting ability (EC50 =11.14 μg/ml) with epidermal growth factor (EGF; NSDSECPLSHDGYCLHDGVCMYIEALDKYACNCVVGYIGERCQYRDLKWWELR) in a murine model of full‐thickness dermal wound. Tylotoin directly enhances the motility and proliferation of keratinocytes, vascular endothelial cells, and fibroblasts, resulting in accelerated reepithelialization and granulation tissue formation in the wound site. Tylotoin also promotes the release of transforming growth factor β1 (TGF‐β1) and interleukin 6 (IL‐6), which are essential in the wound healing response. Gene‐encoded tylotoin secreted in salamander skin is possibly an effector molecule for skin wound healing. This study may facilitate understanding of the cellular and molecular events that underlie quick wound healing in salamanders.—Mu, L., Tang, J., Liu, H., Shen, C., Rong, M., Zhang, Z., Lai, R. A potential wound‐healing‐promoting peptide from salamander skin. FASEB J. 28, 3919‐3929 (2014). www.fasebj.org